Management of Gestational Diabetes Mellitus through Ayurveda – A Case Report - Jyoti Krishnaji Gayakawad; Shashidhar A Naik; Reshma Salimani; Deepika Deepika; K V Mamatha (Journal of Ayurveda and Holistic Medicine (JAHM), 2026)
Background: Gestational diabetes mellitus (GDM) is a common obstetric complication associated with significant maternal, fetal and neonatal morbidity. Conventional management includes medical nutrition therapy (MNT), oral hypoglycemic agents and insulin when required. Ayurveda conceptualizes conditions similar to GDM under Prameha and offers Pathya Ahara-Vihara and Shamanaushadhi. However, systematically documented clinical evidence remains limited. Clinical Findings: A 32-year-old primigravida was diagnosed with GDM at 26 weeks 5 days of gestation based on a 75-g oral glucose tolerance test (OGTT) interpreted according to IADPSG criteria (fasting glucose 116 mg/dL, 1-hour glucose 183 mg/dL, 2-hour glucose 119 mg/dL). She also had mild anemia (Hb 9.8 g/dL). Intervention: Dietary and lifestyle modification was initiated at 26 weeks 5 days of gestation. As fasting and postprandial blood glucose levels remained above target after two weeks, Shamanaushadhi -Dhatri Loha, Vasanta Kusumakara Rasa, and Asanadi Kashaya were started from 28 weeks 5 days and continued until delivery. Outcome: Postprandial blood glucose declined from 157 mg/dL at 28 weeks 5 days to 118 mg/dL at 40 weeks, reaching the recommended postprandial target, while fasting blood glucose remained relatively stable during follow-up. A healthy male neonate weighing 3200 g was delivered by LSCS for non-progress of labor, with APGAR scores of 7, 9, and 10 at 1, 5, and 10 minutes respectively. No neonatal complications or treatment related adverse events were observed. Conclusion: In this case, dietary and lifestyle modification was initiated at 26 weeks 5 days of gestation following the diagnosis of GDM, followed by Shamanaushadhi at 28 weeks 5 days of gestation, and continued until delivery, with follow-up to 6 weeks postpartum. Improvement in glycemic control was observed during treatment, along with favorable maternal and neonatal outcomes and no treatment-related adverse events. This case highlights the potential role of Ayurveda in the management of gestational diabetes mellitus.